2020
DOI: 10.1186/s13287-020-01639-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from human umbilical cord mesenchymal stem cells inhibit vein graft intimal hyperplasia and accelerate reendothelialization by enhancing endothelial function

Abstract: Background: In our previous research, we found that mesenchymal stem cell (MSC) transplantation therapy can inhibit intimal hyperplasia and enhance endothelial function in arterialized vein grafts in rats. However, whether MSC-derived exosomes (MSC-exosomes) can reduce neointimal formation and its possible mechanism is still unclear.Methods: The primary human umbilical cord MSCs (hucMSCs) and human umbilical vein endothelial cells (HUVECs) were isolated and characterized by flow cytometry and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 44 publications
(62 reference statements)
3
40
0
5
Order By: Relevance
“…Many studies have proved that exosomes secreted by MSCs may be a key ingredient of paracrine mechanism to spread its repair function, exosomes can be served as a translocator(miRNAs, lncRNAs, and proteins) that contributes to intercellular communication 26,27 . Our previous studies have found that exosome cargo may account for the vascular protective effect of hucMSCs against vein graft failure 14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have proved that exosomes secreted by MSCs may be a key ingredient of paracrine mechanism to spread its repair function, exosomes can be served as a translocator(miRNAs, lncRNAs, and proteins) that contributes to intercellular communication 26,27 . Our previous studies have found that exosome cargo may account for the vascular protective effect of hucMSCs against vein graft failure 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Isolation, characterization and culture of hucMSCs and HUVECs All experiment protocols were approved by the Ethical Committee of the Qilu Hospital of Shandong University (KYLL-2017-106) as we have described 14 . Human umbilical cords were collected from informed, consenting delivery woman and processed as we have previously described 14 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we assumed that BMSCs might be able to differentiate into enterocytes to repair intestinal epithelial barrier. According to previous reports, PI3K/AKT/mTOR signaling pathway is involved in cell fate and likely to be associated with proliferation and differentiation of stem cells [21,22]. To investigate whether the PI3K/AKT/mTOR signaling pathway is associated with the differentiation of BMSCs into enterocytes, we performed the transwell co-culture system and evaluated the characteristic molecules of enterocytes by immuno uorescence staining.…”
Section: Association Of Pi3k/akt/mtor Signal Pathway In the Differentmentioning
confidence: 99%